Підвищення ефективності керування судновим двомасовим електроприводом - Будашко, В.В. (Електротехніка і електромеханіка, 2016)
На підставі теоретичних і практичних досліджень двомасового електроприводу суднової вантажної системи рефрижераторного судна, в роботі вирішена науково-технічна проблема вдосконалення системи керування електроприводом впродовж впливу на нього різновекторних збурень. Результатом виконаних досліджень є поєднання рівнянь, що
описують переміщення вантажу механізмом підйому рамки утримувача палет, в систему диференціальних рівнянь з
коефіцієнтами, залежними від коливань судна. У теоретичній частині синтезовано математичну модель електромеханічної системи механізму підйому, що дало змогу дослідити способи мінімізації кутів розгойдування і часових
інтервалів, необхідних для стабілізації переміщення вантажу двохмасовим електроприводом механізму підйому, що
дозволило у непрямий спосіб імплементувати сигнал, пов’язаний зі стохастичною природою моменту коливання судна, на координатну площину електроприводу підйому. Також удосконалено та досліджено спосіб параметричної оптимізації математичної моделі електромеханічної системи в функції кута розгойдування вантажу. На підставі визначення структури та алгоритмів роботи підвищена ефективність системи керування двохмасовим електроприводом механізму підйому з точки зору зменшення часу стабілізації рухомого вантажу На основании теоретических и практических исследований двухмассового электропривода судовой грузовой системы
рефрижераторного судна, в работе решена научно-техническая проблема усовершенствования системы управления
электроприводом, находящегося под разновекторными возмущениями. Результатом выполненных исследований является объединение уравнений, описывающих перемещения груза механизмом подъема рамки держателя паллет, в систему дифференциальных уравнений с коэффициентами, зависящими от колебаний судна. В теоретической части
синтезирована математическая модель электромеханической системы механизма подъема, что позволило исследовать способы минимизации углов раскачивания рамки держателя паллет и временных интервалов, необходимых для
стабилизации перемещения груза двухмассовым электроприводом механизма подъема, что дало возможность косвенно имплементировать сигнал, связанный со стохастической природой момента колебания судна, на координатную
плоскость электропривода подъема. Также усовершенствован и исследован способ параметрической оптимизации
математической модели электромеханической системы в функции угла раскачивания груза. На основании определения структуры и алгоритмов работы повышена эффективность системы управления двухмассовым электроприводом механизма подъема с точки зрения уменьшения времени стабилизации перемещаемого груза Purpose. For shipboard lifting and transporting machinery
(LTM) with AC thyristor electric drives (ED) the problem of
minimizing sway through the formation of the special law to
change the principle of ED control over the lifting process is
solved. Methodology. This goal was achieved through the following objectives: analysis of current studies on the reduction of
the negative effects of load fluctuations, fixed on the suspension
with variable parameters; determining the criteria to optimize
the movement of the lifting mechanism and transfer control laws
under which the load fluctuations are reduced; develop the methodology and experimental study of the main characteristics of
the mobile model ED lifting mechanism with its load suspended
from the perspective of both the parameterization of the control
system (CS) as well as elements of ED. For realization of tasks
in research methods of mathematical modeling of dynamic
processes on the computer, structural methods of control theory,
experimental studies in the laboratory setting have been used.
Results. Based on analysis of current research can be concluded
that the stability of the ED of LTM to the disturbing points provided coincidence zero electric coordinates and speed deviation
diametric plane of the vessel from the vertical position. Criteria
for optimizing CS used by the ED LTM mathematical description of its dynamics differential equations to the estimated coefficients derived from the functions of state variables. The experimental dependence of dynamic equations of motion of an
object under the influence of disturbing forces in the coordinate
plane allowed to parameterize characteristic equation to the
form, providing the solution to sustainability since the motor
shaft of LTM. The functional circuit of CS eliminates the aperiodic components in the control in compliance with the criteria
of sustainability and quality of transients by applying all-range
regulator coordinate characteristics of forcing overcoming the
dead zone and increase electric resistance as the dynamic object. Practical value. Completion of the complex research may
find practical application in the ED of ship’s LTM, which will
improve their performance, decrease between the operating and
maintenance simple.